A review of the Tandanicolinae (=Monodhelminthinae) (Digenea: Fellodistomidae), with a description of Prosogonarium angelae n. sp - Cribb, T. H.; Bray, R. A. (Systematic Parasitology, 1994)
The Tandanicolinae is reviewed, redefined and considered a subfamily of the Fellodistomidae. The Monodhelminthinae Dollfus, 1937, Mehratrematinae Srivastava, 1939, Prosogonariinae Mehra, 1963 and Buckleytrematinae Yamaguti, 1971 are synonyms of the Tandanicolinae. Genera included in the Tandanicolinae are Tandanicola, Monodhelmis, Buckleytrema and Prosogonarium. Burnellus and Mehratrema are made new synonyms of Monodhelmis. The composition of each genus is reviewed. Monodhelmis arii Yamaguti, 1952, Mehratrema arii Gu & Shen, 1979, Mehratrema dollfusi Srivastava, 1939, Monodhelmis philippinensis Velasquez, 1961, Mehratrema polynemusinis Chauhan, 1943 and Mehratrema skrjabini Karyakarte, 1969 are considered synonyms of Monodhelmis torpedinis. Monodhelmis elongatus Bilqees, 1970 is considered a species inquirenda. Prosogonarium angelae n. sp. is described from Euristhmus lepturus from Moreton Bay, Queensland. It is distinguished by the number and distribution of the vitelline follicles and the extent of the caeca. New records are given for Monodhelmis torpedinis from Arius graeffei and E. lepturus, M. trichofurcata from Tandanus tandanus, and Buckleytrema indica from A. graeffei, all from southern Queensland. Buckleytrema indica is redescribed and B. postacetabulorchis is synonymised with that species. Relationships within the Tandanicolinae were considered by cladistic analysis.